Structural and functional conservation at the boundaries of the chicken β-globin domain - Saitoh, Noriko (Oxford University Press, 2000)
We show that the 3′ boundary of the chicken β-globin locus bears striking structural similarities to the 5′ boundary. In erythroid cells a clear transition in DNase I sensitivity of chromatin at the 3′ end of the locus is observed, the location of this transition is marked by a constitutive DNase I hypersensitive site (HS), and DNA spanning this site has the enhancer-blocking capacity of an insulator. This HS contains a binding site for the transcription factor CTCF. As in the case of the 5′ insulator, the CTCF site is both necessary and sufficient for the enhancer-blocking activity of the 3′ boundary. The position of this insulator is consistent with our proposal that it may function to maintain the distinct regulatory programs of the globin genes and their closely appended 3′ neighbor, an odorant receptor gene. We conclude that both boundaries of the chicken β-globin domain are capable of playing functionally similar roles and that the same protein is a necessary component of the molecular mechanism through which these boundaries are defined.